Quantum complementarity of clocks in the context of general relativity. (13th August 2018) - Zhou, Zhifan; Margalit, Yair; Rohrlich, Daniel; Japha, Yonathan; Folman, Ron
Abstract: Clocks play a special role at the interface of general relativity and quantum mechanics. We analyze a clock-interferometry thought experiment and go on to theoretically derive and experimentally test a complementarity relation for quantum clocks in the context of the gravitational time lag. The effect of time lag is simulated using a magnetic gradient. We study this relation in detail and discuss its application to various types of quantum clocks.